Identifikasi Hambatan Pelaksanaan Evidence-Based Nursing oleh Perawat - Indra, Rani Lisa; Saputra, Bayu; Sandra, Sandra; Rasyid, T. Abdur (Jurnal Kesehatan Komunitas, 2024)
Implementing evidence-based nursing is an effort to improve the quality of nursing care by applying the best research results in carrying out patient care. However, its implementation still needs to be improved. This study aims to identify barriers to nurses' implementation of EBN. Descriptive research was conducted on 49 nurses in the surgical inpatient room of one of the government hospitals in Pekanbaru City. Data were collected using a questionnaire with a Likert scale. Data were analyzed univariately using frequency distribution. The results of the study found that the main things that hinder the implementation of evidence-based nursing are the number of patients to be treated (69.4%), lack of fluency in English (61.2%), lack of time to study research (53.1%) and lack of knowledge of nurses about scientific evidence-based care (51%).  Workload and personal aspects become obstacles in the implementation of evidence-based nursing by nurses; it may be necessary to recalculate the workload so that the distribution of nurses becomes better and consideration to carry out training related to evidence-based nursing to improve knowledge and practice of evidence-based nursing by nurses.